Oridonin-Loaded Nanoparticles Inhibit Breast Cancer Progression Through Regulation of ROS-Related Nrf2 Signaling Pathway - Zhao, Yue; Xiao, Weiwei; Peng, Wanqing; Huang, Qinghua; Wu, Kunru; Evans, Colin E.; Liu, Xinguang; Jin, Hua (Frontiers in Bioengineering and Biotechnology, 2021)
Oridonin has been shown to inhibit tumor cell growth and proliferation in vitro, while its optimum anti-tumor activity in vivo is limited due to the poor aqueous solubility and bioavailability. In this study, to improve the bioavailability, we developed a nanoparticle based drug delivery system to facilitate delivery of oridonin to breast tumor. Oridonin was encapsulated in biodegradable nanoparticles (NPs) based on poly-lactic-co-glycolic acid (PLGA) and polyethylene glycol (PEG) to form oridonin NPs (ORI-NPs). The resulting ORI-NPs exhibited a mean particle diameter of 100 nm and displayed an efficient cellular uptake by human breast cancer MCF-7 cells. Compared to free oridonin that showed no effects on tumor cell proliferation, the ORI-NPs showed significant cytotoxicity and delayed endothelial cell migration, tube formation and angiogenesis. Pharmacokinetics studies showed that ORI-NPs significantly increased the half-life of oridonin in the blood circulation. In the nude mouse xenograft model, ORI-NPs markedly inhibited tumor growth and angiogenesis, while oridonin did not show any inhibitory effects on the growth of tumor xenografts. The mechanism experiments showed that the antitumor activity of ORI-NPs against breast cancer might be through ROS related Nrf2/HO-1 signaling pathway. Together, these results demonstrated that ORI-loaded PEG-PLGA NPs enhanced bioactivity and bioavailability in vivo over oridonin, indicating that ORI-NPs may represent a promisingly effective candidate against breast cancer.